2022
DOI: 10.3390/ijms24010689
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystallographic Structure, Theoretical Analysis, Molecular Docking Studies, and Biological Activity Evaluation of Binuclear Ru(II)-1-Naphthylhydrazine Complex

Abstract: Ruthenium(II)–arene complexes have gained significant research interest due to their possible application in cancer therapy. In this contribution two new complexes are described, namely [{RuCl(η6-p-cymene)}2(μ-Cl)(μ-1-N,N’-naphthyl)]X (X = Cl, 1; PF6, 2), which were fully characterized by IR, NMR, and elemental microanalysis. Furthermore, the structure of 2 in the solid state was determined by a single crystal X-ray crystallographic study, confirming the composition of the crystals as 2·2MeOH. The Hirshfeld su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 75 publications
2
11
0
Order By: Relevance
“…[32,33] Medium bands between 1500 and 1000 cm À 1 can be assigned to bending vibrations of p-cymene and benzene rings. [31] The same region of spectra of 2 contains a strong band at 1646 cm À 1 (L2•HCl: 1603 cm À 1 ) that belongs to the same mixed mode of bending vibrations. The shift between 1665 and 1646 cm À 1 is due to chlorine's weak positive resonant effect.…”
Section: Ir Spectroscopy (Experimental and Theoretical)mentioning
confidence: 94%
See 2 more Smart Citations
“…[32,33] Medium bands between 1500 and 1000 cm À 1 can be assigned to bending vibrations of p-cymene and benzene rings. [31] The same region of spectra of 2 contains a strong band at 1646 cm À 1 (L2•HCl: 1603 cm À 1 ) that belongs to the same mixed mode of bending vibrations. The shift between 1665 and 1646 cm À 1 is due to chlorine's weak positive resonant effect.…”
Section: Ir Spectroscopy (Experimental and Theoretical)mentioning
confidence: 94%
“…These values are similar to previously crystallographically determined for binuclear Ru(II)-naphthylhydrazine complex with bridging chlorido ligand. [31] The differences between crystalographic and optimized structures are due to the overall system relaxation during optimization. When bond angles are concerned, the change of substituents does not induce significant changes in the spatial arrangement of ligands around Ru(II).…”
Section: Optimization Of Structure Nbo Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The Molecular Operating Environment (MOE) was created with the intention of studying molecular docking and 3D/2D structures [ 20 , 31 , 36 ]. We used the MOE-Dock docking program, and the MOE-implemented ligplot to visualize the protein-ligand interaction.…”
Section: Methodsmentioning
confidence: 99%
“…They observed that the binuclear complexes cause cytotoxicity via the p53 pathway and decrease the invasion ability of breast cancer cells. 21 Two binuclear ruthenium arene complexes with a naphthylhydrazyl ligand have been synthesized and examined for their stability, BSA binding affinity, and cytotoxic activity against prostate PC-3 and colon HT-29 cancer cells by Eichhorn et al 22 Fig. 2 depicts the structures of some previously reported binuclear arene ruthenium complexes.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%